Transformasi dan peluang bisnis digital di indonesia: Implikasi bagi UMKM - Efendi, Muhammad Alief Rafa (Maliki Interdisciplinary Journal, 2025)
Digitalization has transformed traditional business models into information technology-based systems. Digital business offers significant opportunities for MSMEs to increase efficiency, expand market reach, and enhance competitiveness. However, challenges such as the digital literacy gap and lack of access to infrastructure remain obstacles to implementing digital business. This research employed a desk study method through an analysis of literature related to the development of digital business in Indonesia as well as scientific studies from the academic environment of UIN Maulana Malik Ibrahim Malang. The study results indicate that digital transformation in MSMEs requires active collaboration between the government, business actors, educational institutions, and technology providers. Thus, digital business has the potential to become a driving force for the national economy if digitalization barriers can be overcome. Furthermore, research findings confirm that increasing human resource capacity through digital skills training, strengthening the regulatory ecosystem, and providing ongoing mentoring are key factors in driving successful technology adoption in the MSME sector. These efforts not only accelerate the digital transformation process but also ensure that MSMEs are able to adapt to increasingly competitive market dynamics. With the development of technological innovation and increased business readiness, digitalization is expected to create new economic opportunities that are inclusive and sustainable, and support more equitable national economic growth.